2014
DOI: 10.1111/iep.12094
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin potentiates the anti‐tumour effect of pravastatin in rat mammary gland carcinoma model

Abstract: Previous studies in the field of cancer research have suggested a possible role for statins in the reduction of risk in certain malignancies. The purpose of these studies was to examine the chemopreventive effects of pravastatin alone and in combination with pineal hormone melatonin in the N-methyl-N-nitrosourea-induced mammary carcinogenesis model. Pravastatin was given orally (1 00 mg/kg) and melatonin was added to the water (20 μg/ml). Chemoprevention began seven days prior to carcinogen administration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…Another study by El‐Aziz et al reported a significant increase in caspase‐3 activity and DNA fragmentation in breast cancer‐bearing rats treated with melatonin in association with other agents. In another animal study, melatonin in combination with pravastatin noticeable enhanced expression of both caspase‐3 and caspase‐7 in rat mammary carcinoma cells in comparison with pravastatin alone . These results are in contrast with those of Kepka et al, where melatonin was shown to significantly reduce the early and late apoptosis of peritoneal leucocytes, by specifically inhibiting the extrinsic apoptosis pathway.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Another study by El‐Aziz et al reported a significant increase in caspase‐3 activity and DNA fragmentation in breast cancer‐bearing rats treated with melatonin in association with other agents. In another animal study, melatonin in combination with pravastatin noticeable enhanced expression of both caspase‐3 and caspase‐7 in rat mammary carcinoma cells in comparison with pravastatin alone . These results are in contrast with those of Kepka et al, where melatonin was shown to significantly reduce the early and late apoptosis of peritoneal leucocytes, by specifically inhibiting the extrinsic apoptosis pathway.…”
Section: Discussionmentioning
confidence: 72%
“…A large number of studies support the role of melatonin in the developmental and cellular processes, such as haematopoiesis and oxidative damage, while others indicate therapeutic potential, based on demonstrated anti‐angiogenic, anti‐inflammatory, anti‐cachectic, pro‐apoptotic,, immune‐stimulatory, and metabolism‐modulatory activities . In addition, melatonin can potentiate the anti‐tumour effects of other drugs . Although various studies demonstrated a clear anti‐cancer effect of melatonin, it cannot alone cause a complete regression of tumour, indicating the need to identify strategies whereby melatonin could act synergistically (or additively) to potentiate the anti‐cancer effects of other agents.…”
Section: Introductionmentioning
confidence: 99%
“…Statins reportedly have additional benefits including oncostatic actions and antifibrillating and defibrillating potential. Melatonin was found to exaggerate the cancer‐inhibiting actions of pitavastatin and pravastatin against breast cancer in experimental studies. Melatonin also has antiarrhythmic potential equivalent to that of atorvastatin in an isolated heart model .…”
Section: Melatonin As An Antioxidant: Waging War On Free Radicalsmentioning
confidence: 99%
“…The major obstacle in cancer treatments is the resistance acquired by carcinoma cells against current chemotherapy drugs, and there are increasing evidence that ER stress is activated in various solid tumors favoring in part this resistance . There are studies where melatonin acts as a potent therapeutic agent in combination with other drugs to support the efficacy of anticancer agents . Furthermore, disturbances in melatonin production have been reported to drive resistance to tamoxifen .…”
Section: Melatonin In Cancermentioning
confidence: 99%